The Influence Of Social Media On Student Learning Patterns - Angelica Sinaga; Krista bella sihombing; Riyani Tarigan; Sonita Putri Natalia (Outline Journal of Education, 2026)
This study aims to determine the effect of social media use on students' learning patterns, including concentration, study time, learning motivation, and academic interaction. This study used a quantitative approach with a survey method of 30 student respondents from various study programs. The results showed that the majority of students (27 out of 30) used social media for more than three hours per day, especially Instagram, TikTok, and YouTube. Social media use has both positive and negative impacts on learning patterns. Positive impacts include ease of access to digital learning resources, improved academic communication, and the emergence of learning motivation through educational and inspirational content. Meanwhile, negative impacts include decreased concentration, reduced productive study time, and increased distractions due to excessive entertainment content. Overall, the influence of social media on students' learning patterns depends on usage patterns and self-control abilities. Therefore, students need to use social media wisely and productively so that it can play a role as an effective learning support tool in the digital era.